MODEL KOMUNIKASI EFEKTIF DALAM PENGELOLAAN SAMPAH RUMAH TANGGA - Tita Melia Milyane; Rannie Dyah Khatamisari Rachaju (Prodi Ilmu Komunikasi FISIP Universitas Langlangbuana, 2019)
Waste is one of the biggest unsolved problem in Indonesia, and it affect the nation health and surrounding, not only in big city but also in rural area. Wastes are unwanted material at the end of a process. Human defined wastes by its usefulness degree, but by its process through nature, wastes are just a product. Where wastes are just insubstantial material that valueless. Considering that waste problem are important and urgent matter, we need a better waste management that not only efficient but also beneficial, especially in the application of effective communication model. We must remember that this earth is a loan from our next generations that we must conserve for a better tomorrow. Good or bad habitude in waste management will determine the continuity of earth and human nature. Maybe Don’t Litter are just an old saying but it will determine our nature and earth continuity. Because in the end our habitude in waste management are depend on our individual habitual in waste management.